2013
DOI: 10.1088/0957-4484/24/35/355201
|View full text |Cite
|
Sign up to set email alerts
|

Large-area aligned growth of single-crystalline organic nanowire arrays for high-performance photodetectors

Abstract: Due to their extraordinary properties, single-crystalline organic nanowires (NWs) are important building blocks for future low-cost and efficient nano-optoelectronic devices. However, it remains a critical challenge to assemble organic NWs rationally in an orientation-, dimensionality- and location-controlled manner. Herein, we demonstrate a feasible method for aligned growth of single-crystalline copper phthalocyanine (CuPc) NW arrays with high density, large-area uniformity and perfect crossed alignment by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…MPc nanomaterials were found to have outstanding redox and electronic properties that were interesting in gas-sensors applications, active material for molecular electronic devices, photodetectors and photocatalytic catalyst [14][15][16][17][18]. It is found that the gas-sensor performance of MPc strongly depends on its microstructure [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…MPc nanomaterials were found to have outstanding redox and electronic properties that were interesting in gas-sensors applications, active material for molecular electronic devices, photodetectors and photocatalytic catalyst [14][15][16][17][18]. It is found that the gas-sensor performance of MPc strongly depends on its microstructure [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lattice fringes from high resolution TEM (HRTEM) image (Figure 2b) and electron diffraction spectroscopy (EDS) pattern (Figure 2c) reveal that the CuPc nano columns are α-phase single crystalline. The presence of lattice spacing of 1.295 nm indicates that the nano column has (010) planes, 6,14 while the growth orientation is determined to be [010]. According to these results, a representation of the crystal structure (inset in Figure 2c) can be drawn.…”
Section: Resultsmentioning
confidence: 97%
“…These include (i) vapor‐grown ultrapure pentacene single crystal devices with field‐effect mobilities of 15–40 cm 2 V −1 s −1 ; (ii) vapor‐grown rubrene single crystal based OFETs with a mobility of 18 cm 2 V −1 s −1 , which utilized a chemically‐treated dielectric surface to reduce the charge trap density; (iii) a vacuum‐gap field‐effect transistor with a hole mobility of about 10 cm 2 V −1 s −1 by using platelet‐like, thin dinaphtho[2,3‐ b :2′,3′‐f]thieno[3,2‐ b ]thiophene (DNTT) single crystals grown by horizontal physical vapor transport in; and (iv) epitaxy‐grown, two‐dimensional C 8 ‐BTBT crystal‐based OFETs with a mobility of 10 cm 2 V −1 s −1 . Often, the vapor‐based growth process is combined with the template‐assisted approach to control the growth, alignment, and positioning of organic single crystals . Organic single crystals including pentacene, rubrene, tetracene, C 60 , F 16 CuPc, and tetracyanoquinodimethane (TCNQ), have been directly grown on octadecyltriethoxysilane (OTS)‐printed domains (Figure d) .…”
Section: Heterogeneous Integration Of Organic Single Crystalsmentioning
confidence: 99%
“…These approaches facilitated the fabrication of large arrays of high‐performance, single‐crystal OFETs for flexible device applications. In another study, Au film domains were introduced on a substrate to grow vertically‐aligned, single‐crystal copper phthalocyanine (CuPc) . As a result of the high surface energy, CuPc nanowire arrays were grown selectively on the Au film‐coated areas.…”
Section: Heterogeneous Integration Of Organic Single Crystalsmentioning
confidence: 99%